Religious practices and changes in health-related quality of life after hospital discharge for an acute coronary syndrome - Abu, Hawa O. (Health Qual Life Outcomes, 2019)
BACKGROUND: Religious beliefs and practices influence coping mechanisms and quality of life in patients with various chronic illnesses. However, little is known about the influence of religious practices on changes in health-related quality of life (HRQOL) among hospital survivors of an acute coronary syndrome (ACS). The present study examined the association between several items assessing religiosity and clinically meaningful changes in HRQOL between 1 and 6 months after hospital discharge for an ACS. METHODS: We recruited patients hospitalized for an ACS at six medical centers in Central Massachusetts and Georgia (2011–2013). Participants reported making petition prayers for their health, awareness of intercessory prayers by others, and deriving strength/comfort from religion. Generic HRQOL was assessed with the SF-36®v2 physical and mental component summary scores. Disease-specific HRQOL was evaluated using the Seattle Angina Questionnaire Quality of Life subscale (SAQ-QOL). We separately examined the association between each measure of religiosity and the likelihood of experiencing clinically meaningful increase in disease-specific HRQOL (defined as increases by ≥10.0 points) and Generic HRQOL (defined as increases by ≥3.0 points) between 1- and 6-months post-hospital discharge. RESULTS: Participants (n = 1039) were, on average, 62 years old, 33% were women, and 86% were non-Hispanic White. Two-thirds reported praying for their health, 88% were aware of intercessions by others, and 85% derived strength/comfort from religion. Approximately 42, 40, and 26% of participants experienced clinically meaningful increases in their mental, physical, and disease-specific HRQOL respectively. After adjustment for sociodemographic, psychosocial, and clinical characteristics, petition (aOR:1.49; 95% CI: 1.09–2.04) and intercessory (aOR:1.72; 95% CI: 1.12–2.63) prayers for health were associated with clinically meaningful increases in disease-specific and physical HRQOL respectively. CONCLUSIONS: Most ACS survivors in a contemporary, multiracial cohort acknowledged praying for their health, were aware of intercessory prayers made for their health and derived strength and comfort from religion. Patients who prayed for their health and those aware of intercessions made for their health experienced improvement in their generic physical and disease-specific HRQOL over time. Healthcare providers should recognize that patients may use prayer as a coping strategy for improving their well-being and recovery after a life-threatening illness. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12955-019-1218-6) contains supplementary material, which is available to authorized users.